Evidence for Simultaneous Production of J /ψ and Mesons - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Agnew, J. P.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Askew, A.; Atkins, S.; Augsten, K.; et al. (American Physical Society (APS), 2016)
We report evidence for the simultaneous production of J/ψ and mesons in 8.1 fb-1 of data collected at s=1.96 TeV by the D0 experiment at the Fermilab pp¯ Tevatron Collider. Events with these characteristics are expected to be produced predominantly by gluon-gluon interactions. In this analysis, we extract the effective cross section characterizing the initial parton spatial distribution, σeff=2.2±0.7(stat)±0.9(syst) mb.